2015
DOI: 10.1504/ijart.2015.067389
|View full text |Cite
|
Sign up to set email alerts
|

What makes a Pollock Pollock: a machine vision approach

Abstract: Jackson Pollock introduced a revolutionary artistic style of dripping paint on a horizontal canvas. Here we study Pollock's unique artistic style by using computational methods for characterizing the low-level numerical differences between original Pollock drip paintings and drip paintings of other painters who attempted to mimic his signature drip painting style. Four thousands and twenty four numerical image content descriptors were extracted from each painting, and compared using Weighted Nearest Neighbor c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Stork ( 2009b ) later defended Taylor and colleagues and argued that, while one feature in isolation may not be sufficient for the analysis, a combination of multiple fractal measures can provide useful information. Shamir ( 2015 ) used a set of features from biological image analysis (Shamir et al, 2008 ) and reported an accuracy of 93.0% in discriminating between original and non-original drip paintings.…”
Section: Computational Aesthetics: Algorithms and Applicationsmentioning
confidence: 99%
“…Stork ( 2009b ) later defended Taylor and colleagues and argued that, while one feature in isolation may not be sufficient for the analysis, a combination of multiple fractal measures can provide useful information. Shamir ( 2015 ) used a set of features from biological image analysis (Shamir et al, 2008 ) and reported an accuracy of 93.0% in discriminating between original and non-original drip paintings.…”
Section: Computational Aesthetics: Algorithms and Applicationsmentioning
confidence: 99%
“…For instance, it showed that the computer analysis of art is largely in agreement with how art historians view influential links between different schools of European art (Shamir & Tarakhovsky, 2012). It was also used to identify features typical to Jackson Pollock (Shamir, 2015) and show evidence of mathematical similarities between Jackson Pollock and Vincent von Gogh (Shamir, 2012). Another use of the Wndchrm scheme related to automatic analysis of art is the studying of art perception, showing patterns of differences between abstract expressionism and paintings by children and animals (Shamir et al, 2016).…”
Section: Image Analysismentioning
confidence: 85%
“…Thus, we have introduced a method to capture the stylistic characteristics of art in an objective manner. This greatly simplifies the feature extraction process in art, as it has been indicated by Shamir (14,50,51) that a great variety of handcrafted features are necessary to successfully capture the characteristics of art. Our success is due to that fact that we utilized the recently proposed UFLK algorithm (31,38,52), which facilitates the use of a deep learning-like algorithm.…”
Section: Discussionmentioning
confidence: 99%